Safety and security solution for school bus through RFID and GSM technologies - Hasmah Mansor; Tun Mohamad Aqil Mohamad Fadzir; Teddy Surya Gunawan; Zuriati Janin (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
All children throughout the world aged 4 to 17 are going to schools every weekdays. The most common transport used by children is school bus.  In many countries accross the globe, most children uses school bus services to go to school and return back home especially to working parents.  Although safety of their children is always the main concern of all parents especially the young ones, they have to rely on the bus services due to time constraints during working hours. Sometimes parents need to call the bus driver to ensure their children has reached home or school.  This will create inconvenience to bus driver and may lead to other unwanted consequences. Realizing the root of this problem, a school bus safety and security system has been proposed. The school bus safety and security system is a solution based on Short Messaging System that notifies parents if their children have safely arrived at home or school. RFID and GSM technologies are the main technique proposed in this project. RFID is used for several purposes; to identify the children and parents’ contact number, and attendance monitoring through head count system. GSM is used as a commucation platform to inform parents’ on their children’s movement via SMS. Several tests have been conducted to analyse the overall performance of the developed hardware prototype. From the results, it can be concluded that the developed project is successfully identify the children based on their unique ID, send a text message through SMS to parents with required information; and additional feature of attendance checker. The hardware prototype was successfully tested for children’s identification, attendance and SMS notifications to parents. As a consequence, this project could increase the safety and security solution for children travelling with school bus transportation and give parents peace of mind.